STRATEGI PENGELOLAAN DAN PENGEMBANGAN INDUSTRI PERUMAHAN KELAS MENENGAH (STUDY KASUS PT. BARUGA ASRINUSA DEVELOPMENT) - Rusli Rusli; Muhammad Asdar; Abdul Razak Munir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to find out how the external and internal environment that affects the business and management strategies and development of the middle-class housing business is right for PT. Baruga Asrinusa Development in order to continue to survive and develop. This research was conducted at PT. Baruga Asrinusa Development- Bukit Baruga Estate, located in Antang village, Manggala sub-district, Makassar city. Selection of this location is done intentionally (purposive) with the consideration that PT. Baruga Asrinusa Development is one of the longest established developers since 1992 and is also a local developer located in Makassar which currently has many major competitors from local developers and outside developers. The results of this study find that to deal with external threats immediately implement an aggressive strategy strategy that seeks to improve internal conditions of weakness and external threats by utilizing a number of internal strengths possessed and existing external opportunities.